Structural Features of the αβTCR Mechanotransduction Apparatus That Promote pMHC Discrimination - Brazin, Kristine N.; Mallis, Robert J.; Das, Dibyendu Kumar; Feng, Yinnian; Hwang, Wonmuk; Wang, Jia-huai; Wagner, Gerhard; Lang, Matthew J.; Reinherz, Ellis L. (Frontiers in Immunology, 2015)
The αβTCR was recently revealed to function as a mechanoreceptor. That is, it leverages mechanical energy generated during immune surveillance and at the immunological synapse to drive biochemical signaling following ligation by a specific foreign peptide-MHC complex (pMHC). Here we review the structural features that optimize this transmembrane receptor for mechanotransduction. Specialized adaptations include: 1) the CβFG loop region positioned between Vβ and Cβ domains that allosterically gates both dynamic TCR-pMHC bond formation and lifetime; 2) the rigid super β-sheet amalgams of heterodimeric CD3εγ as well as CD3εδ ectodomain components of the αβTCR complex; 3) the αβTCR subunit connecting peptides (CP) linking the extracellular and transmembrane (TM) segments, particularly the oxidized CxxC motif in each CD3 heterodimeric subunit that facilitates force transfer through the TM segments and surrounding lipid, impacting cytoplasmic tail conformation; and 4) quaternary changes in the αβTCR complex that accompany pMHC ligation under load. How bioforces foster specific αβTCR-based pMHC discrimination and why dynamic bond formation is a primary basis for kinetic proofreading are discussed. We suggest that the details of the molecular rearrangements of individual αβTCR subunit components can be analyzed utilizing a combination of structural biology, single molecule FRET, optical tweezers and nanobiology, guided by insightful atomistic molecular dynamic studies. Finally, we review very recent data showing that the preTCR complex employs a similar mechanobiology to that of the αβTCR to interact with self-pMHC ligands, impacting early thymic repertoire selection prior to the CD4+CD8+ double positive thymocyte stage of development.